Transdermal permeation mechanism of sodium deoxycholate aided nano-transfersomes by Differentail Sacnning Calorimetry (DSC) - Mahmood, Syed; Bakhtiar, M. Taher; Mandal, Uttam Kumar (2015)
Transfersomes are lipid based nano-vesicles made of phospholipid and surfactant. Their drug permeation mechanism through the skin has been attributed to the moisture seeking tendency (xerophobia) of the lipid vesicles followed by destabilization of lipid bi-layer in the stratum corneum (SC) by surfactant1. However, structural changes of SC due to surfactant need further elucidation to know the specific role of that surfactant in doing so. The objective of this study was to evaluate drug permeation mechanism of raloxifene loaded nano-transfersomes containing sodium deoxycholate used as a surfactant. Phospholipon® 90G was used as a lipid composition in the nano-formulation2. Three different types of skin i.e. mice, guineapig, and rabbit were used for this study. The SC was detached from the rest of the skin layers with chemical treatment, thoroughly washed, and kept for drying in a vacuum desiccator. The SC samples were subjected to an ex-vivo permeation study of the transfersomal formulation for 8 hours. A control sample was prepared in a similar way, without any formulation treatment. A sample of the SC section was cut, sealed in aluminum hermetic pans and scanned using DSC at a scanning rate of 5°C per minute over the range of 25°C–125°C. The characteristic bi-layer lipid and keratin transition peaks found in the control SC samples were: 75°C, 78°C, and 95°C for mice; 820C, 900C, and 990C for guineapig; and 840C, 920C, 990C for rabbit3. However, upon treatment with sodium deoxycholate aided raloxifene nano-transfersomes, most of the peaks were shifted towards lower melting points and some of them were disappeared. This finding confirmed disruption of lipid bi-layer and denaturation of keratin in the SC layer of the investigated skin samples by nano-transfersomes with sodium deoxycholate. It also established the role of sodium deoxycholate in transdermal permeation of drug loaded nano-transfersomes formulation.